Causes of Sectarian Extremism in Pakistan: an EMIC Prospective of Religious Scholars - Hafiz ur Rehman; Huma Razaq Abbas; Aisha Tahir (International Journal of Integrative Research, 2023)
The purpose for present study is to investigate the reasons of extremism and sectarianism. The Qualitative research design was used to conduct the study. The semi-structured interview guideline was used for data collection. An In-depth analysis of data was done through thematic analysis by [1]. The sample of participants (N=8), male (n=7) & female (n=1) were selected through purposive sampling from different sect scholars. The interview guideline caters the domains opinion about sectarianism, reasons of sectarianism, why Pakistan is unsuccessful to stop it, role of religious extremism in sectarianism, what preventive measures should be taken, role of human cognitions. Further in depth analysis revealed that there are different Islamic views, division of groups, propaganda, lack of faith, use of power, conflicts, cognitions, following the schools of thoughts and force against Islam regarding opinion of sectarianism and the reasons behind the sectarianism are invasion of external factors, lack of control, misuse of religion, emotional propaganda, political influence etc. Results shows revealed that there is positive, negative and neutral opinion about sectarianism like Islamic view, and division of groups.